(untitled) (Research, Society and Development, 2023)
Introduction: The leukemia corresponds to a hematological disease with a short latency period, developing quicker and generating serious impacts on public health. Objective: To gather data on the mortality trend from childhood leukemia in the Brazilian northeast, the time approach is between the years 2009 to 2019. Methodology: Ecological study of temporal period with a quantitative approach. The numbers of deaths of the Brazilian child and youth population were collected and included between the years 2009 to 2019, with an emphasis on the Northeast region. Data were collected between March and April 2022 through the National Cancer Institute’s Online Mortality Atlas. The causes of death analyzed were lymphoid leukemia (C91), myeloid leukemia (C92), monocytic leukemia (C93), type-specified cell leukemias (C94) and unspecified cell type leukemia (C95). Results: Between 2009 and 2019 in the Northeast, there were 16,579 deaths due to leukemia, of which 3,010 were in the infant and youth population, with an annual average of 273.63±19.601. Regarding the age group, the group from 15 to 19 years old had the highest number of deaths, with a total value of 776 deaths. The states of Piauí, Rio Grande do Norte, Sergipe, Ceará and Alagoas had the four highest mortality rates in the region. Conclusion: Studies that seek to identify patterns, whether integrative, systematic or ecological, are essential not only to verify which part of the population is most affected by the disease, but also to know which points still need attention from public policies.